The Building a Culture of Islamic Religious Education Literacy through the School Literacy - Jaenullah, Jaenullah; Laili, Nur; Setiawan, Dedi; Aini, Nur; Abrori, Sayyidul; Haikal, Haikal (International Journal on Advanced Science, Education, and Religion, 2025)
This research is motivated by the challenges faced in literacy levels in Indonesia. According to various international reports, Indonesia’s student literacy index is still relatively low compared to other countries. The low interest in reading and critical understanding hinders the learning process in schools and negatively affects students' academic performance. The aim of this study is to explore the implementation of building a literacy culture in Islamic Religious Education (PAI) lessons through the School Literacy Movement (GLS) in grade V at SDNU Kota Metro, Lampung. Using a qualitative approach, the study involves the principal and grade V teachers at SDNU Kota Metro, Lampung as informants. Data collection techniques include observation, interviews, and document studies, while data analysis uses the Miles and Huberman model, which consists of data collection, presentation, and verification stages. The results indicate that the implementation of the literacy culture in PAI lessons through the School Literacy Movement at SDNU Kota Metro, Lampung has been carried out in accordance with the government program, covering several stages, namely habituation, development, and learning.